Revitalisasi Penilaian Adaptif untuk Mutu Pendidikan Islam Berkelanjutan - Misbahul Arifin; Faiq Julia Iqna’a; Juwita; Arini Nuora Darina; Dian Zulfatul Iman (Khatulistiwa Insight: Islamic Education and Learning, 2025)
This research focuses on the contestation of quality indicators in Islamic education and its implications for the character crisis among students, with the aim of revitalizing and developing adaptive assessment instruments that integrate substantive character and 21st-century competencies. Employing a mixed-methods approach with an exploratory sequential design, a case study was conducted at MA Nurul Jadid Paiton. Data were collected through participant observation, in-depth interviews with the school principal, teachers, committee members, and students, as well as document studies. Thematic analysis was used for qualitative data, while descriptive and inferential statistical analyses were applied to quantitative data. The findings reveal a significant disconnection between conventional quality indicators and the manifestation of a character crisis, such as a lack of initiative, empathy, and resilience, which are not effectively measured by existing instruments. The novelty lies in the design of an adaptive instrument that integrates three dimensions of competence: character, digital literacy and critical thinking. Key data indicate that 76% of teachers believe the current quality indicators do not reflect the realities of character-based learning in the field. Consequently, this research proposes the Islamic Education Quality Assessment Instrument Model Based on Digital Character Ecosystem (IPMBEKD), expected to be a fundamental solution for holistically measuring quality, fostering pedagogical change, and strengthening character formation in the digital age.